The origins of experimental psychology in Lithuania (1910-1940s) - Martynaitis , J. (Psichologija, 1971)
The article describes the first steps of experimental psychology in Lithuania and some of its developmental features in 1910-1940 are discussed. The author describes works of J. Vabalas-Gudaitis, the founder and the head of Kaunas University Laboratory of Experimental psychology, analyzes in detail the improved method for reaction research in the laboratory. While describing this laboratory the author also focuses on the research of V. Lazersonas on latent periods of reaction, fatigue and professional orientation. Author also provides with some knowledge of the history of test use and introduces with tests created by the author.
Keywords: tests; testing; history of psychology; experimental psychology; J. Vabalas-Gudaitis; V. Lazersonas